The Analysis Of Seba Baduy Tradition As A Form Of Indigenous Community Existence - Firman Apriyanto; Titi Julaeha; Susanti Susanti; Madhuri Purba; Eneng Liah Khoiriyah; Iim Khairunnisa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Purpose of Research on Seba baduy conducted by STKIP Sheikh Manshur students in Lebak Regency, aims to get to know more closely the Baduy community in preserving their culture in Seba baduy activities. The research method used is descriptive with a functional approach through data collection techniques in the form of interviews and observations. The result of this research illustrates that Seba Baduy activity is the culmination of a ritual event conducted once a year which is intended to express gratitude to God and the government for the welfare of the Baduy community that has been produced in a period of one year. In addition, Seba Baduy activity has a ritual ceremony, this ceremony is a proof of customary recognition and aims to stay in touch between Kanekes community and the government both in the regency and province, namely to the regent and governor officials who informally become the leaders of Baduy community. The best time and date for the ceremony is chosen, especially after the harvest. The seba ceremony is a series of religious or belief systems of the Sunda Wiwitan religion adopted by the Kanekes community, so this ceremony must be carried out because it is an ancestral heirloom that must continue to be maintained and preserved which is passed on continuously to its children and grandchildren in a firm and binding manner. (Ayuna et al., 2021)